Study of Indentation Response of Functional Graded Al2TiO5- Based Bioceramics - Oo, Zeya; Gorin, Alexander; Low, It-Meng (Jim) (IACSIT Press, 2011)
Aluminium titanate, Al2TiO5 (AT) with the pseudobrookite structure is the only compound in the alumina-titania system. It is an excellent refractory and thermal shock resistant material due to its relatively low thermal expansion coefficient (1 ×10-6 ºC –1) and high melting point (1860ºC). However, its low mechanical strength, hardness and fracture resistance together with susceptibility to decomposition in the temperature range 900–1200ºC has limited its wider application. In this paper, the innovative tailored design of functionally- graded Al2TiO5 – based ceramics system is presented. This involves the use of a vacuum heat-treatment or die-pressing to form hard graded layers of alumina on Al2TiO5. These hard outer layers will provide hardness and wear resistance to protect the softer but damage resistant underlayers. The results will also explore unresolved issues concerning the effect of graded interfaces on their physical and mechanical performance properties.